"This course made me feel guilty to be an Australian": Exterior assemblages and continuing reflections. (10th January 2018) - Crowhurst, Michael; Faulkner, Julie
Abstract : Purpose: From one Graduate Diploma Secondary student taking a pro-diversity course that both authors had a connection with there was a very angry response, encapsulated by the statement "This course made me feel guilty to be an Australian". We are aware that negative student evaluations can be part of the territory for tertiary teachers working in diversity courses. The purpose of this paper is to explore the students' confronting comment which will be construed as a type of offer that is being extended to us – an offer that we are refusing. We draw on Deleuze and Guattari's notion of "exterior assemblages", and we shift our gaze to consider "what constitutes the territory" that is our response to the pre-service teacher's evaluative claim. Design/methodology/approach: The specific methods we deployed involved an eclectic appropriation of various tools. We embarked on this process of exploration by journaling, collective reflection and informal discussions with other colleagues. Our journals responded to the question: What constitutes the place that is the territory that is our refusal of the student's offer? In order to explore this place we: kept a hand-written journal; used conventional text and arts based practice techniques in our journaling; discussed our journal entries periodically (face to face, via Skype and via e-mail); discussed this project with colleagues – giving them knowledge that we were doing this – and that we might write journal entries about these conversations; and read a variety of relevant texts We engaged in these processes for a three month period. At the end of this period we shared journals, and set about the task of analysing them. We engaged in a number of analyses and detailed our findings over the next month. Further, over a longer period of time we engaged with this incident and our journal entries and presented a series of in progress papers at a variety of conferences and seminars. The analysis of the data generated involved discourse analysis and dialogue. Findings: A series of key discourses were identified and listed in the paper. Research limitations/implications: The key identified ideas are briefly linked to a series of implications for practitioners. Practical implications: One of the key practical implications is the suggestion that where disagreements surface in education that one response to such moments might be for the parties to consider where they are located. Social implications: The paper outlines a way of thinking about disagreements that has useful implications when considering issues relating to pedagogical strategies aiming to work towards social justice. Originality/value: The paper is an original response to a critical moment that occurred for two lecturers in pre-service teacher education.